(untitled) (Plant Tissue Culture and Biotechnology, 2010)
An efficient protocol for plant regeneration through multiple shoots induction from shoot tips of Polygonum hydropiper (L.) was established. The highest percentage (96.6) of multiple shoot induction and number of shoots (9.0) per culture were found on MS supplemented with 2.0 mg/l Kn. The induced shoots were excised and inoculated on to MS contains different concentrations of IBA or NAA for rooting. The highest percentage (90.0) of root induction and the highest number of roots per shoot (12.0) was found on MS having 1.0 mg/l IBA. Well rooted plantlets were acclimated properly and transplanted in the soil under natural condition, where cent per cent plantlets survived and grew successfully. Key words: Polygonum hydropiper, Shoot tips, In vitro propagation D.O.I. 10.3329/ptcb.v20i1.5970 Plant Tissue Cult. & Biotech. 20(1): 73-79, 2010 (June)